2007
DOI: 10.1103/physrevd.75.064011
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological perturbations on local systems

Abstract: We study the effect of cosmological expansion on orbits-galactic, planetary, or atomic-subject to an inverse-square force law. We obtain the laws of motion for gravitational or electrical interactions from general relativity-in particular, we find the gravitational field of a mass distribution in an expanding universe by applying perturbation theory to the Robertson-Walker metric. Cosmological expansion induces an (ä/a) r force where a(t) is the cosmological scale factor. In a locally Newtonian framework, we s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(110 citation statements)
references
References 35 publications
(47 reference statements)
8
101
0
1
Order By: Relevance
“…In the same publication, we will constrain the parameters α and n, taking into account the recent data of the ephemerides of the Solar System provided by INPOP10a [31,32] and EPM2011 [33][34][35]. Actually, perturbations in the form of power-law are present in different models of modified gravity, and their impact on the Solar System dynamics has been analyzed, for instance, in [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…In the same publication, we will constrain the parameters α and n, taking into account the recent data of the ephemerides of the Solar System provided by INPOP10a [31,32] and EPM2011 [33][34][35]. Actually, perturbations in the form of power-law are present in different models of modified gravity, and their impact on the Solar System dynamics has been analyzed, for instance, in [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…All the other potentials are power law functions of r . Perihelion precession for such kind of potentials were calculated in, e.g., [59][60][61]. For a potential V (r ) in the form V (r ) = γ r λ , it is found that the extra perihelion precession per orbital period is…”
Section: Perihelion Precessionmentioning
confidence: 99%
“…Another potential source of major systematic uncertainty is represented by the N-body perturbations due to the other planets, especially Jupiter and Saturn. We will, now, demonstrate that, luckily, they can be modeled with sufficiently 2 Park et al [29] use the symbol for the in-plane, unbroken angle ω + cos I . high accuracy.…”
Section: The Perihelion Precessions Of the Planets Of The Solar Systemmentioning
confidence: 99%
“…Moreover, Eq. (4) is a distinctive feature of the modified model of gravity considered here which would be of great help, in principle, in discriminating Verlinde's theory from the anomalous precessions due to other more or less viable alternative models [1,2,14] by taking, e.g., the ratio of the perihelion rates for a pair of planets [14,15]. Table 1 The column˙ theo collects the theoretically predicted perihelion precessions, calculated for some planets of the Solar System according to Eq.…”
Section: Introductionmentioning
confidence: 99%